2002
DOI: 10.1034/j.1600-0773.2002.900505.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant/Restorative Effects of Calcined Gold Preparations Used in Indian Systems of Medicine against Global and Focal Models of Ischaemia

Abstract: Stroke, or ischaemic brain damage, is of great geriatric importance being the third most common cause of death after cancer and heart diseases in developed countries. Despite such high frequency, its management has received inadequate attention. Many studies have shown the role of free radicals in the pathogenesis of ischaemic brain damage. Search for safe and effective antioxidant and free radial scavenger agents, therefore, appear to be a promising approach for stroke therapy. Gold, widely used in modern med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…Balancing the GSH/GSSG level requires an important cofactor, NADPH, which is produced from reactions catalyzed by G-6PD and 6-phosphogluconate dehydrogenase. Thus, GST, GR and G-6PD are secondary antioxidant enzymes that play an important role in detoxifying ROS/RNS by maintaining a ready supply of intermediates such as GSH and NADPH [25]. Decreased activity of GR would directly affect GSH as would a reduction in the levels of GST, resulting in overall low levels of antioxidant defense, thus predicting the overpowering influences of ROS/RNS in brain injuries [7,8,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Balancing the GSH/GSSG level requires an important cofactor, NADPH, which is produced from reactions catalyzed by G-6PD and 6-phosphogluconate dehydrogenase. Thus, GST, GR and G-6PD are secondary antioxidant enzymes that play an important role in detoxifying ROS/RNS by maintaining a ready supply of intermediates such as GSH and NADPH [25]. Decreased activity of GR would directly affect GSH as would a reduction in the levels of GST, resulting in overall low levels of antioxidant defense, thus predicting the overpowering influences of ROS/RNS in brain injuries [7,8,24].…”
Section: Discussionmentioning
confidence: 99%
“…G-6-PD (EC 1.1.1.49) activity was assayed by the method of [25]. Briefly, the assay mixture consisted of 0.05M tris-HCl buffer (pH 7.6), 0.1 mM NADP, 0.8 mM glucose-6-phosphate, 8 mM MgCl 2 and 0.03 ml of PMS in total volume of 1.0 ml.…”
Section: Estimation Of G-6pd Activitymentioning
confidence: 99%
“…RA patients are therefore exposed to oxidant stress (Harris, 2003). Consequently, a number of different activities of antioxidant enzymes, such as superoxide dismutase, glutathione peroxidase, catalase, and glutathione reductase have been reported to be effective in treating RA (Blake et al, 1981;Mazetti et al, 1996;Shah & Vohora, 2002). Some other researchers found that RA patients were more inclined to lipid peroxidation because of the reduced antioxidant defense system (Rowley et al, 1984;Gambhir et al, 1997).…”
Section: Newer Experimental Therapies With Antioxidants Evaluated In Aamentioning
confidence: 99%
“…Therefore there are chances of free radical mediated damage to the body of RA patients due to their higher production or improper scavenging. Thus analysis of activities of different antioxidant enzymes like superoxide dismutase (SOD), catalase, glutathione peroxidase (GSH-Px) and glutathione reductase (GR) may have effective therapeutic potential [11,13,14]. There is more interest in roles of these in the clinical outcomes of disease like RA, therefore, we were interested in analyzing the level of MDA which is product of lipid peroxidation and level of enzymes of free radical scavenger system like superoxide dismutase (SOD), GR, catalase and levels of alkaline phosphatase (ALP) in RA patients treated with MTX, Folic acid Vit-C and occasional corticosteroids.…”
Section: Introductionmentioning
confidence: 99%